Cost-minimization and budget impact analysis of bypassing agents in hemophilia A with inhibitors: a Brazilian study - da Silva Pinto, Christiane Maria; Souza Silveira, André Luis; Carvalho, Fábio; da Silva, Janaina; Bomfim Ribeiro, Tatiane; Vilela de Brito, Gabriela (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
OBJECTIVE: The aim of the study was to compare the treatment with plasma-derived activated prothrombin complex concentrate (APCC) and recombinant activated FVII (rFVIIa) in patients with Hemophilia A with inhibitors, analyzing the costs and budget impact of prophylactic and on-demand treatment in the Brazilian Unified Health System (In Portuguese, Sistema Único de Saúde [SUS]). METHODS: This study performs a Cost-Minimization Analysis (CMA) and a Budget Impact Model) BIM for APCC versus rFVIIa in the prophylaxis and on-demand treatment in SUS perspective, based on analysis of guidelines and public databases from Brazil. RESULTS: The cost per patient for prophylaxis is estimated to be lower with APCC than in rFVIIa for the maximum dose with an incremental cost difference of BRL 2,730,798 (APCC BRL 3,325,894 versus rFVIIa BRL 6,056,692). The BIM estimated that 5 years after the partial substitution of rFVIIa for APCC (30% and 70%, respectively) brings the potential saving of BRL 201,622,888 considering prophylaxis in adults and BRL 83,095,850 in children. For on-demand usage, the amount saved could be BRL 42,696,097 in adults and BRL 17,596,556 in children. CONCLUSION: This analysis suggests a potential cost saving from payer’s perspective (SUS) using APCC instead rFVIIa for Hemophilia A patients with inhibitors, mainly for prophylaxis. The results could potentially bring value to patients and payers as resources could be reallocated to provide more care with the same budget, considering patient clinic response.